1992
DOI: 10.1038/360361a0
|View full text |Cite
|
Sign up to set email alerts
|

Natural inhibitor of transforming growth factor-β protects against scarring in experimental kidney disease

Abstract: The central pathological feature of human kidney disease that leads to kidney failure is the accumulation of extracellular matrix in glomeruli. Overexpression of transforming growth factor-beta (TGF-beta) underlies the accumulation of pathological matrix in experimental glomerulonephritis. Administration of an antibody raised against TGF-beta to glomerulonephritic rats suppresses glomerular matrix production and prevents matrix accumulation in the injured glomeruli. One of the matrix components induced by TGF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
523
2
9

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 946 publications
(554 citation statements)
references
References 16 publications
14
523
2
9
Order By: Relevance
“…Thus, further studies are needed to explore the role of versican in diabetic nephropathy and other glomerular disorders. Our finding of a downregulation of the decorin core protein at D40 is consistent with the notion that this protein binds and neutralises extracellular TGF-β, thus antagonising the prosclerotic effect of this cytokine [45,46]. The biological functions of fibromodulin are largely unknown; however, fibromodulin also binds to active TGF-β [47].…”
Section: Discussionsupporting
confidence: 88%
“…Thus, further studies are needed to explore the role of versican in diabetic nephropathy and other glomerular disorders. Our finding of a downregulation of the decorin core protein at D40 is consistent with the notion that this protein binds and neutralises extracellular TGF-β, thus antagonising the prosclerotic effect of this cytokine [45,46]. The biological functions of fibromodulin are largely unknown; however, fibromodulin also binds to active TGF-β [47].…”
Section: Discussionsupporting
confidence: 88%
“…25,[28][29][30] Decorin has the ability to inhibit TGF-b by forming an inactive complex. 4,31,32 Additionally, it has also been shown that decorin inhibits TGF-b mRNA transcription and TGF-b protein synthesis. 13,33 However, these functions appear to be highly cell-type specific.…”
Section: Discussionmentioning
confidence: 99%
“…Many investigators have focused on TGF-β as a target for therapeutic intervention in experimental renal disease in rats [44][45][46][47][48] (Table 1). Much as it has been proposed that several molecules are involved in the autoregulation of TGF-β in vivo, these particular molecules have been used as targets in renal fibrosis.…”
Section: Transforming Growth Factor-betamentioning
confidence: 99%
“…Decorin in its turn is inactivated by the actions of several MMPs that can cleave it into fragments, liberating TGF-β from the ECM [50]. Intravenous application of decorin in experimental glomerulonephritis prevented TGF-β-mediated matrix accumulation [46]. Another example of an autoregulatory mechanism is the interaction between TGF-β and PAI-1.…”
Section: Transforming Growth Factor-betamentioning
confidence: 99%